Analysis Of Work Discipline In Improving Employee Performance At PT. Perintis Scaleindo Internasional North Jakarta - Tiara, Egis Safa; Harsono, Yhonanda (Pascasarjana Universitas Pasundan, 2025)
This study aims to analyze the role of work discipline in improving employee performance at PT Perintis Scaleindo Internasional, North Jakarta. Work discipline is a key factor in achieving work effectiveness and efficiency, particularly in a company involved in weighing technology services. This research adopts a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings reveal that the implementation of work discipline within the company still faces challenges such as unexcused absences, tardiness, and an imbalance in task distribution due to limited human resources. The dimensions of discipline examined include punctuality and job responsibility, while employee performance indicators cover quality, quantity, timeliness, and accuracy. Although some employees demonstrate commitment and responsibility in performing their duties, a general decline in attendance and work quality has negatively impacted the company's overall performance. This study recommends strengthening the discipline management system, streamlining workflow processes, and increasing the workforce to help the company achieve its organizational goals more effectively.